Perencanaan Floating Club House Sebagai Inovasi Bisnis Pariwisata di Kawasan Pantai Amed, Pulau Bali - Zaidan, Roid Hatta; Rindo, Good; Amiruddin, Wilma; Prasetyo, Naufal Abdurrahman (JURNAL INTEGRASI, 2024)
Amed Beach located in East Bali is a popular tourist destination known for its beautiful beaches and attractive beach clubs. As an innovative effort to support the local economy, a floating club with a futuristic club concept was constructed in this area. The floating club is designed to attract more tourists and aligns with the regional regulations of Karangasem Regency in infrastructure development. Its design takes into account operational capacity on land by calculating displacement, deadweight, and lightweight. The main dimensions of the floating club are LoA = 40 m, B = 40 m, H = 2.25 m, and T = 1.5 m, with a capacity of 200 visitors and 50 crew members per day. Additionally, layout design, general arrangement, and 3D modeling were planned, with a total construction cost of Rp. 23,012,974,239. The floating club is moored using a spread mooring system for stability.